2020
DOI: 10.1093/jas/skaa340
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of standardized ileal digestible lysine utilization for whole body protein deposition in pregnant gilts and sows during early-, mid-, and late-gestation

Abstract: The efficiency of SID Lys utilization (kSID Lys) in gilts and sows during early (d 48-52), mid (d 75-79) and late gestation (d 103-107) was investigated using 88 pregnant females (PIC 1050; 27 gilts, 27 parity 1 sows, 34 parity 2+ sows; 192.96 ± 22.84 kg at d 42 ±1 of gestation) and whole body nitrogen (N) retention balance studies. Females were assigned to one of 4 SID Lys levels ranging from 40 to 70% of the daily SID Lys requirements above maintenance for a parity 1 sow according to the NRC (2012) gestating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The Lys requirement increases as gestation progresses because more Lys is steadily needed for reproductive purposes (Sola-Oriol & Gasa, 2017). A recent study (Ramirez-Camba et al, 2020) reported that maximal Lys utilization efficiency was achieved in pregnant gilts at 7.2, 9.1, and 13.5 g SID lysine/day in early-, mid-, and late-gestation, respectively. They also found that maximal retention of Lys was achieved with a higher Lys supply, namely at 8.5, 10.5, and 20.9 g SID lysine/day in early-, mid-, and late-gestation, respectively.…”
Section: Lysine Intakementioning
confidence: 99%
“…The Lys requirement increases as gestation progresses because more Lys is steadily needed for reproductive purposes (Sola-Oriol & Gasa, 2017). A recent study (Ramirez-Camba et al, 2020) reported that maximal Lys utilization efficiency was achieved in pregnant gilts at 7.2, 9.1, and 13.5 g SID lysine/day in early-, mid-, and late-gestation, respectively. They also found that maximal retention of Lys was achieved with a higher Lys supply, namely at 8.5, 10.5, and 20.9 g SID lysine/day in early-, mid-, and late-gestation, respectively.…”
Section: Lysine Intakementioning
confidence: 99%
“…The increase in milk production occurred without a decrease in milk quality [53]; consequently, Holstein cows increased their daily production of milk fat and protein. Moreover, a reinterpretation of Ramirez-Camba et al [54], which includes data on the effects of lysine intake on nitrogen retention and reproductive performance of 69 pregnant primiparous sows, revealed that dietary SID lysine levels associated with Rmin were related to increased litter size (Figure 7). which includes data on the effects of lysine intake on nitrogen retention and reproductive performance of 69 pregnant primiparous sows, revealed that dietary SID lysine levels associated with Rmin were related to increased litter size (Figure 7).…”
Section: Resultsmentioning
confidence: 90%
“…The increase in milk production occurred without a decrease in milk quality [53]; consequently, Holstein cows increased their daily production of milk fat and protein. Moreover, a reinterpretation of Ramirez-Camba et al [54], The studies considered for investigating the physiological responses captured by the linear-logistic model are listed in Table 1 and detailed below. When data on the effects of rumen-protected methionine supplementation in Holstein cows [53] were fitted with a linear-logistic model, milk production was maximized at AA doses corresponding to the inflection point where weight gain was reduced, or Rmin (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming this AA composition resembles the sow’s actual requirement, dietary treatment effects were attributable to the overall supply of protein and not to any single essential AA. However, it should be kept in mind that of the nine essential AA, Lys has been studied most extensively in gestating sows ( Samuel et al, 2012 ; Ramirez-Camba et al, 2020 ; Thomas et al, 2021 ; Farmer et al, 2022 , 2023 ), while only a few studies have been conducted on the other essential AA [methionine; Bin et al (2018) ; Xia et al (2019) , threonine; Dourmad and Étienne (2002) ; Levesque et al (2011) , tryptophan; Franco et al (2014) and isoleucine; Franco et al (2013) ]. According to Liebig’s law of minimum, the essential AA fed with the most deficit is the limiting factor for AA utilization.…”
Section: Discussionmentioning
confidence: 99%